Radicalisation theories, policing practices, and "the future of terrorism?". Issue 3 (1st September 2016) - Monaghan, Jeffrey; Molnar, Adam
ABSTRACT: This article explores how theories of radicalisation have placed an emphasis on the development of an indicators-based approach to identify individuals who might engage in politically motivated violence. We trace how policing agencies have juxtaposed the search for indicators as a defence against criticisms of racial profiling. However, through an analysis of Canadian counter-terrorism training programmes, we demonstrate that the search for radicalisation indicators reaffirms pre-emptive and discriminatory security practices. We insist that despite efforts to theorise radicalisation outside of the practices of the "war on terror", current trends risk rationalising prejudicial policing that affirms social exclusion and injustice.